PB

Rút gọn biểu thức C = 2( sin4x + cos4x + sin2x.cos2x) 2 - ( sin8x + cos8x)  có giá trị không đổi và bằng

A. 2

B4

C1

D. 0

CT
2 tháng 7 2018 lúc 11:37

Chọn C.

Ta có: C = 2( sin4x + cos4x + sin2x.cos2x) 2 - ( sin8x + cos8x)

= 2 [ (sin2x + cos2x) 2 - sin2x.cos2x]2 - [ (sin4x + cos4x)2 - 2sin4x.cos4x]

= 2[ 1 - sin2x.cos2x]2 - [ (sin2x+ cos2x) 2 - 2sin2x.cos2x]2 + 2sin4x.cos4x

= 2[ 1- sin2x.cos2x]2 - [ 1 - 2sin2x.cos2x]2  + 2sin4x.cos4x

= 2( 1 - 2sin2xcos2x+ sin4x.cos4x) –( 1- 4sin2xcos2x+ 4sin4xcos4x) + 2sin4x.cos4x

=  1.

Bình luận (0)

Các câu hỏi tương tự
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết
H24
Xem chi tiết
PB
Xem chi tiết
DN
Xem chi tiết
DN
Xem chi tiết
HB
Xem chi tiết
PB
Xem chi tiết